2002
DOI: 10.1590/s1519-566x2002000200025
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência de afídeos em alface (Lactuca sativa L.) em cultivo hidropônico

Abstract: -The occurrence of aphids was evaluated on lettuce hydroponically grown at the Escola Agrotécnica of the State University of São Paulo (UNESP) located in Jaboticabal County, State of São Paulo, Brazil, from January to December 1999. The total number of each species of aphids present in weekly samplings performed during the period was found to be correlated with the average temperature recorded within the respective sampling period. The occurrence of three species, Uroleucon ambrosie (Thomas), Myzus persicae (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 1 publication
(1 reference statement)
1
13
0
2
Order By: Relevance
“…These results indicate that under milder temperatures aphids are found in larger numbers in lettuce. These results agree with the findings reported by Auad et al (2002), who concluded that temperature significantly influenced the population density of U. ambrosiae (r = -0.5294), for which 20 ºC is the most suitable temperature in hydroponic lettuce. A decrease in the development period in response to temperature increase is a common response in aphids.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These results indicate that under milder temperatures aphids are found in larger numbers in lettuce. These results agree with the findings reported by Auad et al (2002), who concluded that temperature significantly influenced the population density of U. ambrosiae (r = -0.5294), for which 20 ºC is the most suitable temperature in hydroponic lettuce. A decrease in the development period in response to temperature increase is a common response in aphids.…”
Section: Resultssupporting
confidence: 92%
“…Imenes et al (2000), however, described the occurrence of the same species except N. ribisnigri. In the state São Paulo, Yuki (2000) found a higher incidence of M. persicae, M. euphorbiae, and N. ribisnigri, while Auad et al (2002) reported the occurrence of U. ambrosiae, M. persicae, and M. euphorbiae in hydroponic lettuce. The species found in the present study were collected by Carvalho et al (2002) in a survey carried out in several farms in the state of Minas Gerais.…”
Section: Resultsmentioning
confidence: 99%
“…These programs might also be applied in Brazil. Also, Uroleucon ambrosiae (Thomas, 1878) has become a serious lettuce pest (Auad et al 2002). According to our observations, the pest status of this aphid has increased with the increase of hydroponics system in lettuce crops grown in greenhouses in Brazil.…”
Section: Ephedrus Plagiator (Neesmentioning
confidence: 77%
“…The aphids Macrosiphum euphorbiae (Thomas) and Uroleucon ambrosiae (Thomas) are two of the major pests that regularly attack greenhouse lettuce crops (Auad et al, 2002). U. ambrosiae is an aphid from the Nearctic region, which colonizes a range of Compositae plants in South America (Carvalho et al, 1998), and has increased its status as a pest with the increase in the hydroponic production of lettuce in Brazil (Starý et al, 2007).…”
Section: Introductionmentioning
confidence: 99%